Arguments from Order for Q, Revisited: A New Solution to an Old Method - Tripp, Jeffrey M. (Neotestamentica, 2024)
Quantitative arguments from order examine similarities in the sequencing of textual parallels to strengthen broader arguments for a literary relationship between two texts. However, criteria have rarely been offered for distinguishing between coincidental and significant agreement in order. Data analytics software allows us to create probability distributions to determine minimum thresholds for significant agreement. This study uses these distributions to test arguments from order for Q as a unified source text of material that is unique to Luke and Matthew. After building on Tripp 2013 to discuss problems with the argument from order as it appears in Q scholarship, we nevertheless find (in contrast to my earlier study) that agreements in the sequencing of the double tradition are significant, which is consistent with the Q hypothesis. However, the agreement is not strong enough to rule out alternative hypotheses such as one Gospel's direct dependence on the other or, on the assumption of Matthew's and Luke's independent adaptation of Mark, dependence on multiple smaller source texts. Additional arguments are needed to confirm that Q is best understood as a single text before trying to reconstruct it. Finally, we make suggestions for how these distributions may be used to assess arguments from order across biblical scholarship.